Caracterización de bacterias marinas presentes en suelos de piscinas camaroneras en tiempo de post-cosecha y pre-siembra, luego de la preparación de suelos mediante el metodo de aplicación de fuentes de nitrogeno - Farinango, C.B. (2010)
This project has the purpose to carry out the analysis of microbiology of the shrimp farm Acuario 5 in the times of post to harvest and the pre sowing after to have realized a preparation of the pools with fountains of nitrogen, with this manner to obtain samples and to identify the bacterial population each of the times and this way to carry out statistical tables and make comparisons between populations and the amount of nitrogen administered. The method used is traditional, because it intends to implement a laboratory at the venue, but given as an option specialist laboratories, with this we get 1% of bacterial biomass. In order to give a contribution to the shrimp sector as a reference may have bacteria that determine the quality of their soils and their role by harnessing power to improve their production.